2010
DOI: 10.1167/iovs.09-4121
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Apoptosis in Human Retinal Pigment Epithelial Cells Treated with Benzo(e)Pyrene, a Toxic Component of Cigarette Smoke

Abstract: Genistein, resveratrol, and memantine can reverse the apoptosis and oxidant production generated by B(e)P, a toxic element of smoking. These inhibitors may be beneficial against retinal diseases associated with the loss of RPE cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 54 publications
3
24
0
Order By: Relevance
“…In a study 42 focused on blood flow in contact with reactive surfaces, AOs inhibited platelet activation by specific interactions with target proteins. In a different study 43 that examined the effects of toxic elements in smoking benzo(e)pyrene [B(e)P], combinations of genistein, R, and memantine inhibitors reversed the decreased cell viability, activation of apoptosis markers (caspase‐3/7 and caspase‐9) and increased the production of ROS/reactive nitrogen species in B(e)P‐treated human adult retinal pigment epithelial cell‐19 cultures. These inhibitors could be beneficial against retinal diseases associated with the loss of retinal pigmented epithelial cells 43 …”
Section: Discussionmentioning
confidence: 99%
“…In a study 42 focused on blood flow in contact with reactive surfaces, AOs inhibited platelet activation by specific interactions with target proteins. In a different study 43 that examined the effects of toxic elements in smoking benzo(e)pyrene [B(e)P], combinations of genistein, R, and memantine inhibitors reversed the decreased cell viability, activation of apoptosis markers (caspase‐3/7 and caspase‐9) and increased the production of ROS/reactive nitrogen species in B(e)P‐treated human adult retinal pigment epithelial cell‐19 cultures. These inhibitors could be beneficial against retinal diseases associated with the loss of retinal pigmented epithelial cells 43 …”
Section: Discussionmentioning
confidence: 99%
“…Purified rat RPE cells were seeded in DMEM supplemented with 10% FBS in 96-well plates with or without glass coverslips and incubated at 37°C and 5% CO 2 for 5 to 7 days. Antioxidants resveratrol, lutein, or trolox were used at 30 μM, 50 μM, and 20 μM, respectively, as these concentrations had previously been established to be effective but non-toxic for RPE cells in culture [1517]. They were supplied in complete medium at day 3 and 5 or on day 6 before use of cells on day 7.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study, ARPE-19 cells showed a concentration-dependent decrease in cell viability after exposure to B(e)p.[11] In addition, B(e)p promoted apoptosis through activation of multiple caspases, which could be inhibited by exposure to memantine, resveratrol and genistein. [13]…”
Section: Discussionmentioning
confidence: 99%
“…[12] Furthermore, the damaging effects of B(e)p can be partially reversed by pre-treatment with memantine, resveratrol and genistein. [13] B(e)p with its structure of five fused aromatic rings (PAH) with a high molecular weight[14] can be found in substances besides cigarette smoke including automobile exhaust, charcoal-broiled foods, and incomplete combustion of organic materials. [15]…”
Section: Introductionmentioning
confidence: 99%